The street : a quintessential social public space - Mehta, Vikas, 1966- (Earthscan, 2013)
"How do we make sociable streets? This book shows us how these ordinary public spaces can be planned and designed to become settings that support an array of social behaviors. Through carefully crafted research, The Street systematically examines people's actions and perceptions, develops a comprehensive typology of social behaviors on the neighborhood commercial street and provides a thorough inquiry into the social dimensions of streets"--Provided by publisher.